An 86-Year-Old Female with Mitral Regurgitation and Significant Pectus Excavatum - Tasar, Raphael; Tkebuchava, Sophie; Diab, Mahmoud; Doenst, Torsten (The Thoracic and Cardiovascular Surgeon Reports, 2019)
Background We report the case of minimally invasive mitral valve repair in an 86-year-old female with symptomatic structural mitral regurgitation and severe pectus excavatum.Case Description The case summarizes four areas of repetitive heart team discussions. First, should an 86-year-old patient still be treated invasively? Second, if so, should treatment be interventional or surgical? Third, if surgical, should we replace or repair at that age and fourth which surgical access is best with respect to her chest deformation?Conclusion We chose to surgically repair the valve using a minimally invasive approach. The patient was extubated 3 hours after surgery and discharged after 7 days.
Keywords: mitral regurgitation; mitral valve repair; pectus excavatum